2014
DOI: 10.1155/2014/574285
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leaf Rust Resistance Genes in Selected Egyptian Wheat Cultivars by Molecular Markers

Abstract: Leaf rust, caused by Puccinia triticina Eriks., is a common and widespread disease of wheat (Triticum aestivum L.) in Egypt. Host resistance is the most economical, effective, and ecologically sustainable method of controlling the disease. Molecular markers help to determine leaf rust resistance genes (Lr genes). The objective of this study was to identify Lr genes in fifteen wheat cultivars from Egypt. Ten genes, Lr13, Lr19, Lr24, Lr26, Lr34, Lr35 Lr36, Lr37, Lr39, and Lr46, were detected in fifteen wheat cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Thus, PI272560 may be a promising source of resistance that may replace the currently widely used monogenic, Lr -gene-based, race-specific resistances against P. triticina in wheat that are always in danger to be overcome by emerging new races. Today, more than 70 resistance genes ( Lr -genes) against rust in wheat are known (Imbaby et al, 2014, reviewed by McCallum et al, 2016) but only a few Lr -genes were transferred to wheat cultivars as single genes or in combination (McIntosh et al, 1995; McCallum et al, 2016). However, most of these Lr -genes are race-specific in the sense of the gene-for-gene hypothesis (Flor, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PI272560 may be a promising source of resistance that may replace the currently widely used monogenic, Lr -gene-based, race-specific resistances against P. triticina in wheat that are always in danger to be overcome by emerging new races. Today, more than 70 resistance genes ( Lr -genes) against rust in wheat are known (Imbaby et al, 2014, reviewed by McCallum et al, 2016) but only a few Lr -genes were transferred to wheat cultivars as single genes or in combination (McIntosh et al, 1995; McCallum et al, 2016). However, most of these Lr -genes are race-specific in the sense of the gene-for-gene hypothesis (Flor, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…The genes Lr13, Lr24, Lr34, and Lr36 are the most common resistance genes among all Egyptian wheat cultivars [191]. Of the non-specific genes, the Lr34/Yr18 complex [192], Lr46 [130] and Lr67 [131] are the most commonly introduced genes in global wheat.…”
Section: Distribution Of Lr Genes In Global Wheat Cultivarsmentioning
confidence: 99%
“…triticina infection, and its prevalence causes serious loss in wheat production. Investigations of the host resistance mechanism are the most economical, effective, sustainable and environmentally friendly method of controlling the disease [ 21 ], therefore attracted a lots of attention in the world. Our previous efforts in the molecular mechanism in wheat plants against leaf rust has demonstrated that the Ca 2+ -calmodulin (CaM) signal transduction pathway was involved in hypersensitive response induced by P .…”
Section: Introductionmentioning
confidence: 99%